A study of the white mold disease of eggplant caused by Sclerotinia sclerotiorum and it’s control - Al-Taae, Ali Kareem; Malallah, Lbna Laith (Journal of Kerbala for Agricultural Sciences, 2018)
The results of isolation and diagnosis of white mold disease of eggplant showed that the causal agent was Sclerotinia sclerotiorum (Lib) de Bary. Two isolates of the pathogen were obtained the first was SSB that isolated from greenhouses in Bashika area and the second was SSC from greenhouses of college of agriculture and forestry. The first isolate was more aggressive than the second one,through the test of the pathogenicity for the two isolates of white mold SSB, and SSC. Infection symptoms appeared as a white mycelium growth. Its appearance like a cotton in an infection sites and then expanded to included large parts of infection area. In the infections areas the leaves were seen in touch with the infected branches, and attacking mold was also seen on the infected branch as mycelium growth observed on the surface of plant. Results of the field control for the white mold, showed the superiority of the T. v. biological agent over the rest of the treatments in terms of the average length of the infected area in the main stem, as it prevented the emergence of any infection on the stem and which was not different from the treatment using the Topsin fungicide which resulted in the decrease of the infection to 0.03 cm . The biological agent T.h. came in the second place and was 1.96 cm compared to the control treatment which was 11.33 cm .